The behavior of uncertainty and disagreement and their roles in economic prediction: A panel analysis - Robert W. Rich; Joseph S. Tracy (Federal Reserve Bank of New York, 2017)
This paper examines point and density forecasts from the European Central Bank's Survey of Professional Forecasters. We derive individual uncertainty measures along with individual point- and density-based measures of disagreement. We also explore the relationship between uncertainty and disagreement, as well as their roles in respondents' forecast performance and forecast revisions. We observe substantial heterogeneity in respondents' uncertainty and disagreement. In addition, there is little co-movement between uncertainty and disagreement, and forecast performance shows a more robust inverse relationship with disagreement than with uncertainty. Further, forecast revisions display a more meaningful association with disagreement than with uncertainty: Those respondents displaying higher levels of disagreement revise their point and density forecasts by a larger amount.
Keywords: C10; C20; C40; 330; uncertainty; disagreement; ECB-SPF; density forecasts; point forecasts; forecast accuracy; forecast revisions